ANALISIS KEBUTUHAN BUKU MULTISENSORI UNTUK PEMBELAJARAN LITERASI PAUD - Ningrum, Pandita; Muliastuti, Liliana; Anwar, Miftahulkhairah; Rosa, Helvy Tiana (Universitas Lampung, 2024)
This research aims to analyze the need for multisensory books in the context of early childhood literacy learning. The research method involved a survey and interviews with early childhood teachers. The results analysis showed that multisensory books play an important role in motivating children to learn to read, increasing their engagement, and accelerating the learning process. Factors such as sensory diversity, children's interest in the story, and positive responses to sensory stimuli affect the effectiveness of multisensory books. Although a small proportion of teachers experienced obstacles, the majority did not face obstacles in introducing children's reading literacy with multisensory books. Children's reading literacy with multisensory books. Awareness of the importance of variety in reading books is very important in supporting the development of early childhood literacy. Thus, awareness of the need for a variety of reading books is important in supporting early childhood literacy development Translated with DeepL.com (free version)Penelitian ini bertujuan untuk menganalisis kebutuhan buku multisensori dalam konteks pembelajaran literasi anak usia dini. Metode penelitian melibatkan survei dan wawancara dengan guru PAUD. Hasil analisis menunjukkan bahwa buku multisensori memainkan peran penting dalam memotivasi anak-anak untuk belajar membaca, meningkatkan keterlibatan mereka, dan mempercepat proses pembelajaran. Faktor-faktor seperti keberagaman sensori, ketertarikan anak terhadap cerita, dan respons positif terhadap stimulus sensori mempengaruhi efektivitas buku multisensori. Meskipun sebagian kecil guru mengalami kendala, mayoritas tidak menghadapi kendala dalam mengenalkan literasi baca anak dengan buku multisensori. Kesadaran akan pentingnya variasi dalam buku bacaan menjadi hal yang sangat penting dalam mendukung pengembangan literasi anak usia dini. Dengan demikian, kesadaran akan kebutuhan akan beragam buku bacaan menjadi penting dalam mendukung pengembangan literasi anak usia dini. Keywords: sensory stimulation, multisensory, early childhood literacy.